Antitrinitarianism and unitarianism in the early modern world - Bem, Kazimierz 1977-; Gordon, Bruce 1962- (Palgrave Macmillan, 2024)
Zusammenfassung: This collection offers an innovative and fresh interpretation of Antitrinitarian and rational dissent in the early modern world. The central themes focus on the fierce debates surrounding Antitrinitarianism and Unitarianism that emerged from the Reformation and the lived cultures of these dissenting movements. The chapters take an interdisciplinary approach addressing ideas in context, their reception and appropriation, and the diverse and often conflicting visions of Christianity. Drawing on previously unused sources, many from Eastern Europe and often in inaccessible languages, this book challenges our understanding of dissent as marginal and eccentric and places it at the center of contesting convictions about the nature of religious reform. Kazimierz Bem is Pastor of First Church in Marlborough (UCC), USA and a senior lecturer in Church History at the Evangelical School of Theology in Wrocław, Poland. Bruce Gordon is Titus Street Professor of Ecclesiastical History at Yale Divinity School, USA
Keywords: Geschichte 1550-1850; Europe--History--1492-.; World history.; Theology.; Philosophy, Modern.; Christian philosophy.; Christianity and culture.; Unitarier; Antitrinitarismus; Europa; History of Early Modern Europe.; World History, Global and Transnational History.; Christian Theology.; Early Modern Philosophy.; Christian Philosophy.; Christian Cultural Studies.; Aufsatzsammlung